2016
DOI: 10.2298/sos1602191a
|View full text |Cite
|
Sign up to set email alerts
|

Some features of sintering of tungsten powders

Abstract: A method of activating the sintering process for tungsten powders using a closed reaction space and hydrogen, steam-saturated water was observed. This sintering process is allowed to activate super coarse-grained (1000 µm) tungsten powder sat relatively low temperatures (1000-1200 °C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…J. Kurtz et.al. [10] in his own study also reported more shrinkage in case of W-Ni heavy alloy. Since tungsten has less self-diffusion, the presence of Ni in the W leads to the phenomenon called Oswald ripening which results in the high density of the W-Ni system.…”
Section: Results and Discussion 31 Effect On Densificationmentioning
confidence: 76%
See 1 more Smart Citation
“…J. Kurtz et.al. [10] in his own study also reported more shrinkage in case of W-Ni heavy alloy. Since tungsten has less self-diffusion, the presence of Ni in the W leads to the phenomenon called Oswald ripening which results in the high density of the W-Ni system.…”
Section: Results and Discussion 31 Effect On Densificationmentioning
confidence: 76%
“…Sintering was done in a vacuum chamber and a constant pressure of 20 MPa was applied on the punches throughout the process. For all the composition, sintering was done at 1200°C [10]. The heat rate was controlled by an automatic heat controller with a set value of 1200°C/min.…”
Section: Sinteringmentioning
confidence: 99%